Digital Da’wah in the Modern Era: The Role of NU Garis Lucu, AISNU, and Pondok Sanad in Engaging the Younger Generation - Nawawi, Taosyekh; Sumiati, Wina (Digital Muslim Review, 2024)
The digitalisation of da’wah refers to the utilisation of online platforms such as Instagram, TikTok, YouTube, Facebook, and Twitter to disseminate Islamic teachings. This transition from traditional to digital da’wah is being embraced by three online Islamic communities: NU Garis Lucu, AISNU, and Pondok Sanad. The primary question this study addresses is: How do these online da’wah communities employ digital platforms to propagate Islamic teachings, and how do consumers of digital da’wah respond to these methods? The study aims to analyse the da’wah methods employed by these communities and to explore how consumers of digital da’wah engage with them, including their preferences and the platforms they favour. A mixed-methods approach, combining both qualitative and quantitative research, is employed. Qualitative data is gathered through interviews with community members and consumers of digital da’wah, alongside direct observations of the activities of the three communities. For the quantitative component, a survey of 100 respondents examines their reactions to digital da’wah. The findings reveal that NU Garis Lucu, AISNU, and Pondok Sanad adopt gentle, non-violent methods (Al-mauizah hasanah) and tailor their approaches to different contexts (Al-hikmah). The methods employed by these communities were generally well received by the respondents.